The Molecular Oxygen Density Structure of the Lower Thermosphere as Seen by GOLD and Models. Issue 8 (26th April 2022) - Greer, K. R.; Laskar, F.; Eastes, R. W.; Lumpe, J.; Liu, H.‐L.; Pedatella, N.
Abstract: Oxygen chemistry plays a central role in the production of plasma in the ionosphere. While molecular oxygen (O2 ) is the third most abundant constituent in the thermosphere, molecular and atomic oxygen densities are difficult to quantify accurately. Consequently, modeled densities have significant uncertainties. New stellar occultation measurements from the Global‐scale Observations of Limb and Disk (GOLD) mission provide data that can quantify, with high precision, the O2 density and its daily and local time variations. These observations are compared to the Mass Spectrometer Incoherent Scatter radar family of empirical models and the physics based Whole Atmosphere Community Climate Model with thermosphere‐ionosphere eXtension. While GOLD observations show a strong diurnal structure with local time, the models display a semidiurnal structure in O2 . The local time structure of O2 is critical for accurately modeling plasma densities in the ionosphere. Plain Language Summary: This paper compares new observations from the Global‐scale Observations of Limb and Disk mission of molecular oxygen (O2 ) in the lower thermosphere (130–200 km in altitude) to widely used models in the aeronomy community. The main finding is that the local time structure of the observed O2 has a minimum at 6 hr local time and a peak near 18 hr local time while the models all show a structure that has peaks at both 6 and 18 hr local time. This significant difference not only influences the total neutral thermospheric density results from the models, but may ultimately impact the calculated ionospheric plasma density and its temporal variability. Understanding ionospheric plasma densities is vital for the proper modeling of the propagation of communications and navigational signals. Key Points: Global‐scale Observation of Limb and Disk molecular oxygen (O2 ) density indicates a diurnal local time structure, while empirical and numerical models have a semidiurnal structure Seasonal variability in O2 density is important for understanding the local time structure Observed vertical O2 density structure has discrepancies with models, with larger differences at 170 km than 140 km